TECHNOPRENEURS AS A STRATEGY FOR UKM EMPOWERMENT IN GLOBAL MARKET COMPETITIVENESS DURING THE COVID-19 PANDEMIC - Farida Rohmah, Alif Risyanto (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2021)
Global Market in ASEAN countries that are already familiar. An increase in competitiveness is a solution in dealing with the current free market. Not only that, during a pandemic like this, Small and Medium Enterprises are expected to be able to compete and maintain their economic resilience. However, the phenomenon that occurs in Small and Medium Enterprises in Karanganyar Village, Batang Regency is the competitiveness of SMEs in Karanganyar Village related to global markets, namely human resources, places of business, stimulant assistance from the government, and a decrease in sales volume during the COVID-19 pandemic. So that it becomes a challenge for the Village Government and the surrounding community. Therefore, there are 3 programs as a solution to empower convection SMEs in Karanganyar Village by improving the quality of human resources through capital building and technopreneur. The purpose of this study is to find out how the government's role in overcoming global economic challenges during the Covid-19 pandemic. This study uses a qualitative method with a descriptive approach. Based on the research results, the potential and role of the Village Government is very large for the development of SMEs with strategies implemented through Capacity Building and Technopreneur. This provides opportunities for SMEs who have limitations in maintaining their business in facing the global market during the Covid-19 Pandemic.